Genomic Characterization of the Japanese Indigenous Wine Grape Vitis sp. cv. Koshu - Tanaka, Keisuke; Hamaguchi, Yu; Suzuki, Shunji; Enoki, Shinichi (Frontiers in Plant Science, 2020)
Vitis sp. cv. Koshu is indigenous to Japan and used as a table and processing grape. It also constitutes an important grape cultivar in Japanese white wine making and is phylogenetically distinct from European grapes. To understand its genomic information, we compared its small and structural variations with those of the table grape cultivar “Thompson seedless” and European wine grape cultivar “Tannat” via a short-read-based resequencing approach. The Koshu genome exhibited high heterozygosity compared to these cultivars, with this characteristic being particularly prominent on chromosome 7. Furthermore, Koshu structural variation encompassed the most and largest extent of duplications and the fewest and smallest extent of deletions with regard to copy number variation and the fewest absence variations among the compared grape cultivars. Plant disease resistance related to cell death associated with hypersensitive response and environmental stress response, such as water deprivation, oxidative stress, and cell wall organization, was inferred through enrichment analysis of small and structural variations. Variant accumulation levels in Koshu indicated that phenylpropanoid, flavonoid, glutathione, and α-linolenic acid pathways were related to polyphenol and flavor components. Together, this Koshu genomic information provides a foundation for improving the quality of Koshu wine and may facilitate the use of Koshu as a genetic resource.